Endoscopic resection for gastric stromal tumor with diameter of 2 to 5 cm - CAI Hongyan; LI Tingzan; ZHANG Yang; AI Xiaoming (Zhongguo linchuang yanjiu, 2023)
Objective To evaluate the clinical efficacy of endoscopic resection for the patients with 2-5 cm gastric stromal tumor (GST). Methods A retrospective analysis was made on the clinical data of 42 patients with 2-5 cm GST who underwent endoscopic surgery in BenQ Medical Center Affiliated to Nanjing Medical University from January 2017 to January 2021. The patients' characteristics, the procedures of endoscopic resection, intraoperative conditions, postoperative recovery and prognosis as well as intra- and post-operative complications were analyzed. Results Endoscopic resection was successfully completed in 38 cases and failed in 4 cases. The surgical specimens were removed successfully in 34 cases and after being cut into pieces in the gastric cavity in 8 cases. Among all lesions completely removed, there were 38 cases with negative margins and 4 cases with positive margins. The intraoperative perforation occurred in 18 cases, including 4 cases of accidental perforation and 14 cases of active perforation. There were 7 cases of massive intraoperative bleeding, 5 cases of postoperative perforation, 4 cases of significant postoperative bleeding and 6 cases of postoperative infection. One case was found to have multiple abdominal metastases 2 years after surgery, but still survived with the tumor. Conclusion For GST with diameter of 2-5 cm, endoscopic resection surgery has a significant therapeutic effect, but the difficulty and risk of operation also increase significantly. Endoscopists need to master a variety of endoscopic procedures and skills, and seek surgical support in time if necessary.